PENGARUH PENGGUNAAN AR (AUGMENTED REALITY) TERHADAP PEMAHAMAN MATERI RANGKA MANUSIA PADA KELAS XII TUNARUNGU DI SLB NEGERI WONOGIRI - Elsa Edhri Raja Siwi; Tias Martika; Tutik Saniatin Zahro (Universitas Sebelas Maret, 2025)
In the 21st century, technological advancements have rapidly transformed various sectors, including education. This study investigates the implementation of Augmented Reality (AR) as a supportive media in the learning process of the Human Skeleton topic within the Science. Employing a Classroom Action Research (CAR) methodology, this study was conducted with four hearing-impaired students in grade XII at SLB Negeri Wonogiri. The findings indicate that AR-based media significantly enhances the effectiveness of the learning process. However, it is also evident that not all students are able to fully assimilate information through technology-based media alone, as some require concrete objects to facilitate their understanding. This suggests the need for a balanced integration of both technological and tangible learning aids to accommodate diverse learner needs